ANALISIS DINAMIK MODEL PENYEBARAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) DENGAN PENGARUH TERAPI - NINGTIAS, YESINTA KHARISMA; QOMARUDIN, M. NUR HAQQUL; AKBARITA, RACHMADANIA; ROBBY, RIZKA RIZQY (E-Jurnal Matematika, 2026)
Dengue Hemorrhagic Fever (DHF) is a viral infectious disease transmitted through the bite of the Aedes aegypti mosquito. This study analyzes the equilibrium effect of therapy in controlling the spread of DHF. A mathematical modeling approach is used to predict the dynamics of the spread of DHF by considering the intervention of therapy use. This model describes the interaction between human population and the effectiveness of therapy. The results of the analysis with a disease-free equilibrium . While the endemic equilibrium point is  with . Stability is achieved when the eigenvalue is less than zero. Disease-free stability is said to be stable when the value of  and endemic stability is said to be stable when the value of . The results of the traveling wave in the model have a minimum speed with . In this case, with the existence of this minimum speed, the wave of spread in the future can occur again needs to be watched out for properly. By carrying out therapy, it is hoped that it can help infected individuals.